Pengaruh Ekstrak Buah Adas (Foeniculum vulgare) terhadap Pertumbuhan Bakteri Salmonella typhi Secara In Vitro - Akbar, Muhammad Zakky Putra; Wijaya, Sofyan Musyabiq; Carolia, Novita; Sukohar, Asep (CV. Jasa Sukses Abadi, 2024)
Bacterial infections, especially those caused by Salmonella typhi, are a global health challenge, including in Indonesia, where there is a high prevalence of typhoid fever. Treatment of this infection generally relies on antibiotics, but increasing antibiotic resistance is becoming a big problem. Therefore, there is a need for alternative treatments that are safer and more effective. This study aims to evaluate the ability of ethanol extract of fennel fruit (Foeniculum vulgare) to inhibit the growth of Salmonella typhi. Extraction was carried out using the maceration method using 70% ethanol, followed by evaporation of the solvent to obtain a stock solution. The extract concentrations tested included 5%, 10%, 20%, 40%, and 80%, with distilled water as a negative control and antibiotics as a positive control. Antibacterial testing was carried out using the disk diffusion method on Mueller Hinton Agar media, and the inhibition zone was measured after 48 hours of incubation. The results showed that fennel fruit extract effectively inhibited the growth of Salmonella typhi at an extract concentration of 20%, with the diameter of the inhibition zone increasing as the concentration increased, reaching 4.75 mm at a concentration of 80%. Statistical tests with Kruskal-Wallis showed significant differences between treatments. This research proves that ethanol extract of fennel fruit has antibacterial potential which can be used as an alternative in treating Salmonella typhi infections, especially considering that it is safer than synthetic antibiotics.